PENERAPAN MODEL BLENDED LEARNING PADA PEMBELAJARAN MATEMATIKA DI SMP FRATER DON BOSCO TOMOHON - Pamela Sumual; victor Sulangi; ihdar Domu (ABDIMAS: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
ABSTRACT. This research was conducted to describe the students learning outcomes who were taught using the Blended Learning model and face to face methods on the relations and functions lesson. The research was conducted at SMP Frater Don Bosco in the odd semester of the 2019/2020 academic year. The research subjects were students of class VIII A as an experimental class taught using the Blended Learning model and students of class VIII B as a control class taught using the face to face method. Data collection in this research used test and data analysis used t-test of differences mean of the two groups. The research result, shows that the average student learning outcomes taught using the Blended Learning model were higher than the average learning outcomes of students who are taught using face-to-face methods on the material relations and functions. Keywords: Blended Learning, Face to Face, Relationships and Functions